DEMOGRAPHIC TRANSITION AND THE ROLE OF URBAN POPULATION IN UZBEKISTAN - Z.N, Tojiyeva. Z.N (International Journal of Psychosocial Rehabilitation, 2020)
The article provides a brief overview of theoretical and methodological issues of population growth and distribution. It also provides detailed demographic updates on demographic processes, “demographic modernization”, demographic transition cycles and how it goes in countries such as Uzbekistan.